Assessment of medical students’ attitude towards didactic lectures taken in pharmacology in a private medical college - A., Umamaheswari; M. S., Umamageswari; A. T., Sathiya Vinotha (International Journal of Basic & Clinical Pharmacology, 2017)
Background: To assess the attitude of second year medical students towards the teaching Principles in Pharmacology didactic lecture classes. Methods: It was a descriptive epidemiological and questionnaire based study. Second year students who were attending pharmacology lecture classes for a period of one month (nearly 8 lectures) were given questionnaire and ask to fill it by assessing the theory classes which was conducted throughout that month. Each question was graded with mark and finally total score was converted to 50 marks. Five-level Likert’s criteria were used to analyze few questions in the questionnaire. Data were analyzed by frequency distribution. Results: Out of 115 students who attended the questionnaire session, 61% students were having a very good and better attitude towards the faculty talking Pharmacology lecture classes and remaining students have a few lacking areas in the teaching mode which should be analyzed. Conclusions: Students have good attitude towards the faculty taking didactic lectures and the lacking areas can be future improved by efficient planning of interactive and interesting lecture methods for the usefulness of students as well as the teacher.